EVALUASI PELAKSANAAN EDUKASI PERLINDUNGAN KONSUMEN BANK INDONESIA MELALUI PROGRAM GEBER PK 2024 - Mustafainal Aqyar Samsu Dwiputra; Muizu, Wa Ode Zusnita (Universitas Bina Taruna Gorontalo, 2025)
This research aims to evaluate the Gerakan Edukasi Bersama Perlindungan Konsumen (GEBER PK) 2024 program by Bank Indonesia, implemented through digital platforms such as TikTok and Instagram. The program needs evaluation to improve its performance in educating the public about personal data protection for consumers. The evaluation method involves benchmarking, including performance analysis (engagement, views), gap identification, and improvement implementation. Data was collected through internal social media activities such as views, likes, comments, and shares, as well as data from similar programs like the Literasi Keuangan program by Otoritas Jasa Keuangan. The evaluation results show that GEBER PK successfully reached a wide audience, especially through TikTok, although engagement rates on some platforms remain low. Comparison with the Literasi Keuangan program by Otoritas Jasa Keuangan also indicates lower engagement for GEBER PK. Strategic recommendations include improving content interactivity on TikTok and Instagram, more intensive promotion on YouTube, and using effective infographics. Overall, the program has effectively utilized digital platforms but still requires optimization for maximum results.